Ethical considerations in investigating youth alcohol norms and behaviours: a case for mature minor consent. (28th September 2015) - Hildebrand, J.; Maycock, B.; Comfort, J.; Burns, S.; Adams, E.; Howat, P.
Abstract : Mature minor consent only became available in Australia in 2007. There is neither an explicitly defined protocol, nor a clear definition evident in the literature relating to use of the mature minor concept in health research. Due to difficulties in defining fixed age ranges to varying levels of maturity and vulnerability, there is a lack of clarity surrounding when it might be reasonable and ethical to apply for or grant a waiver for parental consent. This paper describes the challenges faced and solutions created when gaining approval for use of mature minor consent in a respondent‐driven sampling (RDS) study to explore the social norms and alcohol consumption among 14–17‐year‐old adolescents (n = 1012) in the community. The University's Human Research Ethics Committee granted mature minor consent for this study, and the techniques applied enabled recruitment of adolescents from community‐based settings through use of RDS to achieve the required sample. This paper has relevance for research that requires a waiver for parental consent; it presents a case study for assessing mature minors and makes recommendations on how ethical guidelines can be improved to assist human research ethics application processes.